Income Growth of New Immigrants in Canada: Evidence from the Survey of Labour and Income Dynamics - Banerjee, Rupa (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2009)
SummaryThe present study examines the income growth of newly arrived immigrants in Canada using growth curve modeling of longitudinal data. The results from this study indicate that recent immigrants, regardless of visible minority status, face initial earnings disadvantage. However, while immigrants of European origins experience a period of “catch up” early in their Canadian careers, which allows them to overcome this earnings disadvantage, visible minority immigrants do not enjoy such a catch-up. This racial difference in recent immigrants’ income growth is found to be caused by the fact that visible minority immigrants receive lower returns to education, work experience and unionization. Furthermore, visible minority recent immigrants face greater penalties for speaking a non-official first language than do their white counterparts.